A simple and convenient method to synthesize N-[(2-hydroxyl)-propyl-3-trimethylammonium] chitosan chloride in an ionic liquid. (5th October 2015) - Yang, Xiaodeng; Zhang, Chuanguang; Qiao, Congde; Mu, Xueli; Li, Tianduo; Xu, Jinku; Shi, Lei; Zhang, Dongju
Highlights: HTCC was synthesized using AmimCl as a homogeneous and green reaction medium. The organic solvents, such as AmimCl, ethanol and acetone could be recycled. The reaction mechanism between chitosan and EPTAC in AmimCl was proposed based on the data of theoretical calculations. The work provides insight into the synthesis of HTCC under homogeneous and environment-friendly reaction conditions. Abstract: N -[(2-Hydroxyl)-propyl-3-trimethyl ammonium] chitosan chloride (HTCC) was synthesized through nucleophilic substitution of 2, 3-epoxypropyltrimethyl ammonium chloride (EPTAC) onto chitosan using ionic liquid of 1-allyl-3-methylimidazole chloride (AmimCl) as a homogeneous and green reaction media. The chemical structure of HTCC was confirmed by FTIR, 1 H NMR and 13 C NMR. The FTIR peak intensity of amino group at 1595 cm −1 decreased and that of − N ( C H 3 ) 3 + at 1475 cm −1 increased with the increase of reaction time, confirming the substitution of EPTAC on CS. The degree of substitutions (DS) were calculated from the integral area of 1 H NMR, and the optimum reaction condition was obtained, namely, reaction time of 8 h, temperature of 80 °C and n EPTAC / n − NH 2 of 3/1. The degree of crystallinity and thermal properties of HTCC were characterized by XRD, TG, DSC, and DMA methods. Data from XRD, TG, DSC and DMA show that the degree of crystallinity, thermal stability, as well as glass transition temperature of HTCC decreased with the increase of DS. The reaction mechanism of chitosan with EPTAC in AmimCl was elucidated by performing density functional theory (DFT) calculations.